IL-13Rα2 Is Involved in Resistance to Doxorubicin and Survival of Osteosarcoma Patients - Maryam Karamikheirabad; Junyue Zhang; Ae-Ri Ahn; Ho Sung Park; See-Hyoung Park; Young Jae Moon; Kyoung Min Kim; Kyu Yun Jang (MDPI AG, 2024)
Background/Objectives: Interleukin 13 receptor alpha 2 (IL-13Rα2) is a receptor with a high affinity for IL-13 and is involved in the progression of human cancers. However, studies on the role of IL-13Rα2 in osteosarcoma are limited. Therefore, this study aimed to investigate the expression and roles of IL-13Rα2 in the progression of osteosarcoma. Methods: This study evaluated the roles of IL-13Rα2 in osteosarcomas by evaluating tumor tissues from 37 human osteosarcomas and osteosarcoma cells. Results: Immunohistochemical positivity of IL-13Rα2 was an independent indicator of shorter overall survival and relapse-free survival of 37 osteosarcoma patients and 26 subpopulations of patients who received adjuvant chemotherapy with multivariate analysis. In U2OS and KHOS/NP osteosarcoma cells, overexpression of IL-13Rα2 significantly increased proliferation, migration, and invasion of cells, all of which decreased with knockdown of IL-13Rα2. Overexpression of IL-13Rα2 increased expression of TGF-β, snail, cyclin D1, and BCL2 but decreased BAX, and knockdown of IL-13Rα2 caused a decrease in expression of these molecules. In addition, both in vitro and in vivo, proliferation of osteosarcoma cells increased, and apoptosis decreased with overexpression of IL-13Rα2 under treatment with doxorubicin. Knockdown of IL-13Rα2 sensitized osteosarcoma cells to the cytotoxic effect of doxorubicin. Conclusions: The results of this study suggest that the expression of IL13Rα2 might be used as a potential prognostic indicator in osteosarcoma patients. Furthermore, it is observed that IL13Rα2 influences the resistance to the chemotherapeutic agent doxorubicin. Therefore, a therapeutic trial targeting IL13Rα2 might be a new therapeutic strategy for osteosarcoma, especially those highly expressing IL13Rα2.